A Comparative Evaluation of Anti-Inflammatory and Antiplaque Efficacy of Citrus Sinesis Mouthwash and Chlorhexidine Mouthwash - Mandal, Aritra; Manohar, Balaji; Shetty, Neema; Mathur, Aditi; Makhijani, Barkha; Sen, Nandini (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Citrus sinesis belongs to Rutaceae family is an enriched source of vitamin C, flavonoid compounds and antioxidants are helpful in reducing inflammation. Few in-vitro studies the ethanolic extract of orange peels has successfully reduced periodontal pathogens which has influenced us to prepare a mouth wash with ethanolic extract of orange peel. Aim: To evaluate and compare the effect of indigenously prepared 4% ethanolic extract of Citrus sinseis (Orange peel) mouthwash to commercially available 0.2% Chlorhexidine mouthwash as an anti-plaque agent. Materials and Methods: Twenty subjects in the age group of 18-60 years with moderate to severe gingivitis were divided into two equal groups. Clinical parameters like Plaque Index, Sulcus Bleeding Index and Gingival Index were recorded at baseline, 7th and 14th day respectively. Following oral prophylaxis Group-I (n= 10) subjects were instructed to rinse twice daily with 10ml of 0.2% chlorhexidine mouthwash and Group-II (n= 10) subjects were instructed to rinse twice daily with 10ml of 4% ethanolic extract of Citrus sinesis mouthwash for 14 days. All the subjects were recalled on the 7th and 14th day for follow up to record the clinical parameters. Results: Citrus sinesis 4% mouthwash was seen to be as efficient as 0.2% Chlorhexidine in reducing Plaque Index and more effectively reducing gingival inflammation and gingival bleeding index. Conclusion: Citrus sinesis 4% mouthwash can be used for short term purpose without any potential side effects as an alternative to 0.2% Chlorhexidine mouthwash in reducing plaque and gingival inflammation.